Hubungan Karakteristik individu dan Perilaku Caring Perawat Dengan Kepuasan pasien di Ruang Rawat Inap RSUD Abdul Manap Jambi Tahun 2019 - Ernawati Ernawati; Bettywati E Tumanggor (Universitas Batanghari Jambi, 2020)
Nursing services have a big role to play in improving and determining the quality of health care. caring is an important component in nursing and is at the core of nursing practice because it contains humanistic values, respects human freedom of choice, emphasizes on improving ability and self-reliance, increasing knowledge and respecting every human being. Nurses who have value and caring spirit will have work behaviors that are in accordance with the principles of ethics due to the care of nurses who view clients as humanistic beings so motivated to provide high quality nursing services. This study is a quantitative study with a design description of correlation with a cross sectional approach to view the relationship of individual characteristics and caring behavior of nurses as independent variables and patient satisfaction as variable dependent. The goal is to know the relationship of individual characteristics and behavior of caring nurses with the satisfaction of inpatients of Abdul Manap Jambi Hospital. Samples of patients treated in the first and VIP inpatient rooms, how to take samples by accidental sampling. Data processing with chi-square analysis. Based on the results of the study the characteristics of individuals are mostly: male gender respondents (56.7%), low education (83.3%), age over 46 years (56.7%), and work (61.7%). Caring behavior of nurses is mostly well behaved (73.3%) and 70% of patients are satisfied with the services provided in the inpatient room of RsUD Abdul Manap Kota Jambi. The results of bivariate analysis there is no relationship of individual characteristics with the satisfaction of inpatients and there is a relationship of caring behavior of nurses with the satisfaction of inpatients in Abdul Manap Hospital Jambi City (p value 0.018). The results of the study are expected to improve the quality of nursing services, especially in providing nursing care by taking into account caring aspects to improve the satisfaction of inpatients. For nurses in the inpatient room consistently and further improve caring application in providing nursing care to patients especially in the fulfillment of basic needs and health education in the inpatient room.